Child mental illness and the help-seeking process: a qualitative study among parents in a Ugandan community - V. Skylstad; A. Akol; G. Ndeezi; J. Nalugya; K. M. Moland; J. K. Tumwine; I. M. S. Engebretsen (BMC, 2019)
Abstract Background Child mental illness contributes significantly to the burden of disease worldwide, and many are left untreated due to factors on both the provider and user side. Recognising this, the Ugandan Ministry of Health recently released the Child and Adolescent Mental Health (CAMH) Policy Guidelines. However, for implementation to be successful the suggested policy changes must resonate with the service users. To better understand the sociocultural factors influencing parental mental help-seeking, we sought insights from parents in the Mbale district of eastern Uganda. Method In this qualitative study, eight focus group discussions were conducted with mothers and fathers in urban and rural communities. Parents of children younger than 10 years were purposively selected to discuss a vignette story about a child with symptoms of depression or ADHD as well as general themes relating to child mental illness. The data were analysed using qualitative content analysis. Results Descriptions of severe symptoms and epileptic seizures were emphasised when recognising problem behaviour as mental illness, as opposed to mere 'stubbornness' or challenging behaviour. A mixture of supernatural, biomedical, and environmental understandings as underlying causes was reflected in the help-seeking process, and different treatment providers and relevant institutions, such as schools, were contacted simultaneously. A notion of weakened community social support structures hampered access to care. Conclusion Awareness of symptoms closer to normal behaviour must be increased in order to improve the recognition of common mental illnesses in children. Stakeholders should capitalise on the common recognition of the importance of the school when planning the upscaling of and improved access to services. Multifactorial beliefs within the spiritual and biomedical realms about the causes of mental illness lead to multisectoral help-seeking, albeit without collaboration between the various disciplines. The CAMH Policy Guidelines do not address traditional service providers or provide a strategy for better integration of services, which might mean continued fragmentation and ineffective service provision of child mental health care.